The antioxidant, anti-inflammatory, and antiplatelet effects of Ribes rubrum L. fruit extract in the diabetic rats - KAYA, ÖZLEM TUĞÇE; ŞEKERLER, TURGUT; ŞEN, ALİ (My University, 2022)
The prothrombotic and inflammatory state plays a significant role in the occurrence of cardiovascular complications in type 2 diabetes mellitus. In this study, the antidiabetic, anti-inflammatory, and antiplatelet potentials of the extracts obtained from Ribes rubrum were investigated. The antidiabetic, anti-inflammatory, and antioxidant activities of the ethanol and water extracts of R. rubrum were evaluated by in vitro methods. The total phenolic and flavonoid contents were also determined. The experimental diabetes model in rats was induced with streptozotocin (STZ). After hyperglycemia occurred, the ethanol extracts of R. rubrum (RRE, at 100 mg/kg and 500 mg/kg doses) were administered to the treatment groups for 14 days. Blood glucose, lipid profile, plasma, and pancreas tumor necrosis factor-alpha (TNF-alpha) levels were determined and compared at the end of the experiments. P-selectin levels and mitochondrial membrane polarization (MMP) of platelets were also measured. In vitro study, the RRE showed potent anti-inflammatory activity. Administration of RRE (at 100 mg/kg doses) to diabetic rats lowered blood glucose level insignificantly. The results showed that there was an increment in levels of TNF-alpha in plasma and pancreas tissue of the diabetic group compared to the control group. R. rubrum extract regulated and normalized their levels in plasma and pancreatic tissue. RRE at both doses significantly decreased platelet P-selectin levels and prevented STZ-induced loss of MMP in platelets. The results of current research indicate that RRE extract has potent anti-platelet and anti-inflammatory effects and may be beneficial in preventing diabetic complications. Practical applications Hyperglycemia causes dyslipidemia, advanced oxidative stress, platelet activation, and inflammation in diabetes mellitus. Plants with various medicinal properties are of worldwide interest for the treatment of diseases due to their biological activities. In this study, the antidiabetic, anti-inflammatory, and antioxidant effects of extracts of Ribes rubrum (%100 ethanol, 50% ethanol, water) were evaluated by in vitro and in vivo methods. The diabetes model was induced with streptozotocin (STZ). The rats were divided into control, diabetic control, R. rubrum-100 mg/kg, and R. rubrum-500 mg/kg doses groups. Blood glucose levels, tumor necrosis factor-alpha (TNF-alpha), platelet P-selectin levels, mitochondrial membrane polarization of platelets were examined. The present study has shown that R. rubrum has anti-inflammatory and antiplatelet activity. R. rubrum may be beneficial in the prevention and treatment of DM complications due to its anti-inflammatory and antithrombotic effects.
Keywords: Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Food Engineering; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Engineering and Technology; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); GIDA BİLİMİ VE TEKNOLOJİSİ; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); FOOD SCIENCE & TECHNOLOGY; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE); Biochemistry, Genetics and Molecular Biology (miscellaneous); Clinical Biochemistry; Cancer Research; Molecular Biology; Drug Discovery; Aging; General Biochemistry, Genetics and Molecular Biology; Food Science; Biochemistry; Structural Biology